The ultrastructure of the starfish skeleton is correlated with mechanical stress - Raman; Labisch, Susanna; Dirks, Jan-Henning (Acta biomaterialia, 2025)
Echinoderms and vertebrates both possess mesodermal endoskeletons. In vertebrates, the response to mechanical loads and the capacity to remodel the ultrastructure of the skeletal system are fundamental attributes of their endoskeleton. To determine whether these characteristics are also inherent in Echinoderms, we conducted a comprehensive biomechanical and morphological study on the endoskeleton of Asterias rubens, a representative model organism for Echinoderm skeletons. Our analysis involved high-resolution X-ray CT scans of entire individual ossicles, covering the full stereom distribution along with the attached muscles. Leveraging this data, we conducted finite element analysis to explore the correlation between mechanical loads acting on an ossicle and its corresponding stereom structure. To understand the effects of localized stress concentration, we examined stereom regions subjected to high mechanical stress and compared them to areas with lower mechanical stress. Our results show that the stereom microstructure, both in terms of thickness and orientation, corresponds closely to the mechanical loading experienced by the ossicles. Additionally, by comparing the stereom structures of ossicles in various developmental stages, we assessed the general remodeling capacity of these ossicles. Our findings suggest that the ability to adapt to mechanical loads is a common feature of mesoderm endoskeletons within the Deuterostomia taxonomic group. However, the material remodelling may be a specific trait unique to vertebrate endoskeletons. This study shows a correlation between the ultrastructure and the mechanical stress in the starfish endoskeleton, suggesting that this fundamental structure-function relationship may be an ancestral feature of not only vertebrate endoskeletons. However, unlike vertebrate skeletons, not all starfish ossicles remodel in response to changing stress, indicating a potential divergence in skeletal adaptation mechanisms. Our methodological approach combines morphometrics and finite element modeling and thus provides a powerful tool to investigate biomechanics in complex skeletal structures. [Display omitted]